The Effect Of Product Quality, Price, And Quality Of Service On Consumer Satisfaction Of Kampoengan Duck In Pangkalpinang City - Hamdan Hamdan; Muhammad Egar Zambi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study aims to determine the effect of product quality, price and service quality on customer satisfaction either partially or simultaneously at Bebek Kampoengan. This is a descriptive research with quantitative methods. Data was collected using questionnaires and documentation. The population is consumers who visit and buy a product at Bebek Kampoengan. a sample of 87 respondents who were selected using a non-probability sampling technique with incidental sampling. The analysis technique used is multiple linear regression. The results show that both partially and simultaneously, product quality, price, and service quality affect customer satisfaction. The most dominant influence is product quality on customer satisfaction.